(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
Autologous fat grafting (lipofilling) is widely used in reconstructive and aesthetic surgery; however, variability in clinical outcomes remains a significant challenge. Recent evidence suggests that, beyond surgical technique, the success of fat graft engraftment is largely influenced by the patient’s immunological status and the presence of subclinical inflammation.